Investigation of numerical and experimental behavior of infill walls under out-of-plane impact load - Savas, Sedat; Orhan, Mevlut Emre (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2025)
During earthquakes, infill walls (IW) frequently interact with the reinforced concrete (RC) frames that surround them, despite the fact that they are considered to be non-structural components. In the event that the in-plane and out-of-plane behaviors are mixed together, this interaction has the potential to result in a variety of failure scenarios. In order to develop effective strengthening solutions to prevent collapse and improve their performance in future earthquakes, as well as to reduce their seismic vulnerability, it is crucial to understand the out-of-plane non-linear behavior of IWs. For this reason, the contribution of infill panels should be taken into account in the structural response analysis of existing buildings. The influence of IWs on the seismic performance of reinforced concrete structures is a complex issue. The justification for this is because the interaction between the IW and the frame system is still insufficiently understood. This study addresses the intricate topic already referenced. On January 24, 2020, a magnitude Mw 6.8 earthquake transpired in the middle of Sivrice (Elazig). Upon examination of the earthquake-affected structures, it is observed that the IWs are significantly compromised, and it is presumed that the dynamic loads exerted on the structure are predominantly mitigated by the IWs. This study examined the reaction of the IW subjected to out-of-plane dynamic loads. This study examined the performance of IWs under out-of-plane dynamic loads, considering variables such as plastered versus unplastered IWs, the size effect of the IW, and the presence or absence of a door gap. Experiments were conducted on the walls of two earthquake-damaged carcass structures, which were subsequently modeled and assessed using the ANSYS software, followed by verification. The displacement data on the wall's rear, resulting from the out-of-plane load applied to the walls, were acquired by image processing techniques utilizing a MATLAB.
Keywords: Infill wall; out of plane; earthquake; impact effect; finite element model; image processing methods